2018
DOI: 10.2147/idr.s173455
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antimicrobial resistance mechanisms in carbapenem-resistant <em>Pseudomonas aeruginosa</em> carrying IMP variants recovered from a Mexican Hospital

Abstract: PurposePseudomonas aeruginosa infections in hospitals constitute an important problem due to the increasing multidrug resistance (MDR) and carbapenems resistance. The knowledge of resistance mechanisms in Pseudomonas strains is an important issue for an adequate antimicrobial treatment. Therefore, the objective was to investigate other antimicrobial resistance mechanisms in MDR P. aeruginosa strains carrying blaIMP, make a partial plasmids characterization, and determine if modifications in oprD gene affect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
(74 reference statements)
3
13
0
Order By: Relevance
“…Carbapenemases are encoded by genes that are horizontally transferable by plasmids or transposons and commonly associated with genes encoding for other resistance determinants [30]. Carbapenemases, such as IMP- (Imipenem-resistant Pseudomonas), GES- (Guiana extended-spectrum beta-lactamase), VIM- (Veron integron-encoded metallo-beta-lactamase), and OXA-type (oxacillin-hydrolyzing), have been reported in clinical isolates of P. aeruginosa from patients in a hospital in Mexico [31,32]. On the other hand, our Imipenem resistance rates were higher than those reported for the clinical isolates from patients in ICU of a hospital in Saudi Arabia (38.2%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenemases are encoded by genes that are horizontally transferable by plasmids or transposons and commonly associated with genes encoding for other resistance determinants [30]. Carbapenemases, such as IMP- (Imipenem-resistant Pseudomonas), GES- (Guiana extended-spectrum beta-lactamase), VIM- (Veron integron-encoded metallo-beta-lactamase), and OXA-type (oxacillin-hydrolyzing), have been reported in clinical isolates of P. aeruginosa from patients in a hospital in Mexico [31,32]. On the other hand, our Imipenem resistance rates were higher than those reported for the clinical isolates from patients in ICU of a hospital in Saudi Arabia (38.2%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…In a Mexican hospital, a significant increase in carbapenem resistance was found between 2011 and 2015, and 96% of carbapenem-resistant K. pneumoniae expressed KPC [69]. In a study by López-García, detection of IMP and GES enzymes was reported in carbapenem-resistant P. aeruginosa ; however, some of the strains had multiple mechanisms present simultaneously, such as MBLs and loss of porin expression, resulting in extremely high meropenem minimum inhibitory concentrations [70]. Among A. baumannii strains, the most common carbapenemase enzymes corresponded to OXA enzymes in this region [27], including OXA-23, OXA-58, OXA-72, OXA-143, and OXA-253; however, NDM-1, VIM-1, IMP-1, and IMP-10 have also been detected.…”
Section: Geographic Distribution Of Carbapenem Resistance Mechanismsmentioning
confidence: 99%
“…Also, Pae-97 contains a class 1 integron, but with a different arrangement with IMP-1 allele (without OXA nor gcuD genes). Other studies found multiple strains carrying both IMP-18 and OXA-2 (without gcuD nor aacA4) as part of In169 (Sánchez-Martinez et al, 2010) and In1215 (López-García et al, 2018) integrons, including some located in plasmids. Other integrons, such as In96, In614, and In707, have other alleles and arrangements of the same genes (Martínez et al, 2012).…”
Section: Discussionmentioning
confidence: 98%